Please answer the questions below
Attachments:
![](https://hi-static.z-dn.net/files/d31/8383bf4b87f7717f88552e1c4397718a.jpg)
Answers
Answered by
1
Answer:
Step-by-step explanation:
4.(i)8-27b³-343c³-126bc
=(2)³+(-3b)³+(-7c)³-3(2)(-3b)(-7c)
=(2-3b-7c)[(2)²+(-3b)²+(-7c)²-(2)(-3b)-(-3b)(-7c)-(-7c)(2)]
=(2-3b-7c)(4+9b²+49c²+6b-21bc+14c)
(ii)x²-y²+6y-9
=(x)²-[y²+9-6y]
=(x)²-[(y)²+(3)²-2(y)(3)]
=(x)²-(y-3)²
=[(x)+(y-3)][(x)-(y-3)]
=(x+y-3)(x-y+3)
(iii)125a³+b³+64c³-60abc
=(5a)³+(b)³+(4c)³-3(5a)(b)(4c)
=(5a+b+4c)[(5a)²+(b)²+(4c)²-(5a)(b)-(b)(4c)-(4c)(5a)]
=(5a+b+4c)(25a²+b²+16c²-5ab-4bc-20ca)
HOPE IT HELPS
MARK AS BRAINLIEST
nishabora264:
Thanks
Similar questions
Math,
8 months ago
Science,
8 months ago
Math,
8 months ago
Social Sciences,
1 year ago
Math,
1 year ago